Herramientas tic y su incidencia en el enfoque pedagógico constructivista de la carrera de Educación Básica de la Universidad Técnica de Babahoyo, periodo diciembre 2022 - abril 2023 - Vaca Castellano, Nicolle Bivilet (2023)
The main objective of this research work is to determine the ICT tools and their impact on the constructivist pedagogical approach of students in the basic education career from November 2022 to April 2023. It should be emphasized that ICT tools have become an essential instrument in society due to their great productivity in daily life services. The development or advancement has allowed to prioritize and provide tools for meaningful learning. It allows adapting the needs and favoring autonomy for the audacity to solve concerns and provide a good training to autonomous and critical students. The type of method used in this research is the mixed approach, that is to say, qualitative and quantitative, with which it was possible to reach a precise report to answer the study's problematic. In the results obtained, it was evident the need to include activities where students can develop and explore their creativity with the help of ICT tools, such data were obtained through a survey generated with the Google forms tool. To culminate the research work, it was concluded that the interest of students is related to the type of teaching mechanism applied by the teacher to teach their content.